2021
DOI: 10.1016/j.eclinm.2021.100895
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of dapagliflozin on renal oxygenation and perfusion in type 1 diabetes with albuminuria: A randomised, double-blind, placebo-controlled crossover trial

Abstract: Background: Inhibitors of the sodium-glucose cotransporter 2 (SGLT2) slow the progression of diabetic kidney disease, possibly by reducing the proximal tubule transport workload with subsequent improvement of renal oxygenation. We aimed to test this hypothesis in individuals with type 1 diabetes and albuminuria. Methods: A randomised, double-blind, placebo-controlled, crossover trial with a single 50 mg dose of the SGLT2 inhibitor dapagliflozin and placebo in random order, separated by a two-week washout perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 50 publications
1
46
1
1
Order By: Relevance
“…Although the data presented by Laursen et al [5] fit perfectly with the hypoxia hypothesis, one should remain cautious with their interpretation. First, the authors investigated patients with type 1 diabetes and whether their results can be extrapolated to patients with type 2 diabetes remains to be demonstrated.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Although the data presented by Laursen et al [5] fit perfectly with the hypoxia hypothesis, one should remain cautious with their interpretation. First, the authors investigated patients with type 1 diabetes and whether their results can be extrapolated to patients with type 2 diabetes remains to be demonstrated.…”
mentioning
confidence: 76%
“…In an article published in EClinicalMedicine, Jens Christian Laursen and colleagues present the results of a randomized, double-blind, placebo-controlled crossover study assessing the acute effects of a high dose of dapagliflozin on kidney tissue oxygenation and perfusion in patients with diabetes [5]. In this study, 15 patients with type 1 diabetes and albuminuria and a mean estimated glomerular filtration of 73 ml/min/m 2 were enrolled and randomized to receive consecutively either a single dose of 50 mg dapagliflozin or a placebo with a two-week wash-out period between the two administrations.…”
mentioning
confidence: 99%
“…There are also possibly complementary mechanisms. SGLT2 inhibitors improve tubular oxygenation and reduce tubular hypoxic stress 10 . MRAs reduce renal fibrosis and glomerulosclerosis by deactivating the mineralocorticoid receptor in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cortical perfusion was consistently lower (28%-50%) in CKDand diabetic kidney disease (DKD) populations (Gillis et al, 2016;Li et al, 2017). ASL-MRI found no acute change in perfusion after a single dose of dapagliflozin in T1DM patients (Laursen et al, 2021). Also, in newly diagnosed T2DM patients, perfusion did not change after a 24-weeks treatment with 100 mg canagliflozin, despite a persistent eGFR-reduction (Zhou et al, 2021).…”
Section: Arterial Spin Labeling Mrimentioning
confidence: 99%
“…Although primarily used in cardiology (Gatehouse et al, 2005;Nayak et al, 2015), PC-MRI recently showed reduced RBF in CKD patients vs. healthy controls (Khatir et al, 2014;Khatir et al, 2015). In Type I diabetes (T1DM) patients, PC-MRI showed an acute RBF decrease following a single dose of 50 mg dapagliflozin, although not significantly different from the control group (Laursen et al, 2021).…”
Section: Phase-contrast Mrimentioning
confidence: 99%